2021
DOI: 10.3390/buildings11120616
|View full text |Cite
|
Sign up to set email alerts
|

Factors Driving BIM Learning Performance: Research on China’s Sixth National BIM Graduation Design Innovation Competition of Colleges and Universities

Abstract: With the popularization and rise in BIM technology usage, BIM education for undergraduate students in architecture, engineering, and construction (AEC) related disciplines has emerged as a priority. This study assesses the BIM learning outcomes of students participating in the National BIM Graduation Design Innovation Competition of Colleges and Universities. In total, 2777 valid questionnaire responses were obtained for this study. The Cronbach’s alpha coefficient method and principal component factor analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…As a result, their learning can be improved. For example, research by Ao et al [ 1 ] showed that the teacher’s guidance significantly positively impacts students’ BIM learning performance. In addition, students’ learning behavior can be positively influenced by facilitating their access to the required resources from the school library or online resources while learning BIM technology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, their learning can be improved. For example, research by Ao et al [ 1 ] showed that the teacher’s guidance significantly positively impacts students’ BIM learning performance. In addition, students’ learning behavior can be positively influenced by facilitating their access to the required resources from the school library or online resources while learning BIM technology.…”
Section: Discussionmentioning
confidence: 99%
“…The construction industry has recently adopted Building Information Modeling (BIM). Moreover, research and education on BIM technology have become a prevalent topic for builders and educators in the construction industry [ 1 , 2 ]. Relevant research shows that the popularization and application of BIM technology have undergone a significant transformation in the architecture, engineering, and construction (AEC) industry, which has increased the employment competition of fresh graduates of those majors [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The construction industry has changed from traditional construction practice to BIM-based practice [ 1 ]. As the second revolution of the construction industry, BIM technology has effectively promoted the sustainable development of the construction industry [ 2 ].…”
Section: Introductionmentioning
confidence: 99%